Dehumanization of cyclists predicts self-reported aggressive behaviour toward them: A pilot study. (April 2019) - Delbosc, Alexa; Naznin, Farhana; Haslam, Nick; Haworth, Narelle
Highlights: Conducted a pilot test of the dehumanization of cyclists. Around half of non-cyclists view cyclists as 'less than fully human' Dehumanization measures were significantly correlated with aggression toward cyclists. 'Dehumanization of cyclists' concept deserves further research. Abstract: Cycling provides many benefits to individuals and society, yet in many countries attitudes toward cyclists are largely negative. Public and humorous references to violence against cyclists are not uncommon and a significant minority of cyclists report harassment and aggression. We hypothesize that these hostile attitudes and behaviours are caused, in part, by the dehumanization of cyclists among some individuals . Dehumanization refers to any situation where people are seen or treated as if they are less than fully human. This paper presents a pilot study applying two validated dehumanization measures to a road user group for the first time. We found that the dehumanization measures were internally consistent, showed good discriminant validity (compared to general attitudes to cyclists) and were associated with self-reported aggression toward cyclists. The findings suggest that dehumanization is a concept that deserves further exploration in contexts where cyclists are a minority group. If we can put a human face to cyclists, we may improve attitudes and reduce aggression directed at on-road cyclists. This could result in a reduction in cyclist road trauma or an increase in public acceptance of cyclists as legitimate road users.